2020
DOI: 10.1177/1557085120939658
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Victim Advocates and Predictors of Service Referral Among Law Enforcement Personnel

Abstract: Limited research exists on police officers’ service provision for sexual and domestic violence survivors after they formally report. This study used surveys from 452 commissioned officers at an urban police department in one of the five largest and most diverse U.S. cities to examine police perceptions of victim advocates, self-reported frequency of referral, and predictors of service referral among police. Findings revealed officers were relatively likely to provide referrals and held somewhat favora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Patriarchal socialization has promoted traditional gender norms within heterosexual relationships and excused partner violence (see Johnson, 1997;Martin, 1975). This has influenced schema surrounding DV and can impact the manner in which police respond (Franklin et al, 2019;Goodson et al, 2020), including their attributions of severity, seriousness, and culpability. Indeed, empirical studies have documented police officers' dearth of understanding regarding the complex psychological dynamics of relationship abuse.…”
Section: Schema Theory and Police Response To Domestic Violencementioning
confidence: 99%
See 4 more Smart Citations
“…Patriarchal socialization has promoted traditional gender norms within heterosexual relationships and excused partner violence (see Johnson, 1997;Martin, 1975). This has influenced schema surrounding DV and can impact the manner in which police respond (Franklin et al, 2019;Goodson et al, 2020), including their attributions of severity, seriousness, and culpability. Indeed, empirical studies have documented police officers' dearth of understanding regarding the complex psychological dynamics of relationship abuse.…”
Section: Schema Theory and Police Response To Domestic Violencementioning
confidence: 99%
“…Research has suggested police have been inconsistent in providing service referral information to DV victims who present for assistance (Corcoran et al, 2001;Goodson et al, 2020;Jones & Belknap, 1999;Kernic & Bonomi, 2007;Oppenlander, 1982;Ruff, 2012;Swerin et al, 2018). Early research reported DV referrals in 3% to 4% of calls for service (Ferraro, 1989;Oppenlander, 1982).…”
Section: Service Referral Among Police Personnelmentioning
confidence: 99%
See 3 more Smart Citations